GAMBARAN POSTUR KERJA DENGAN METODE RAPID ENTIRE BODY ASSESMENT PADA BORNEO LAUNDRY DI BALIKPAPAN - Anggraeni , Aulia Anggraeni (IDENTIFIKASI, 2020)
Borneo Laundry is a business that is engaged in laundry or laundry services. Workers in Borneo Laundry, who are mostly female workers, work from Monday to Saturday with working hours of 8-12 hours/day, where based on preliminary observations it was found that some workers were working with odd work postures, so it has the potential to cause musculoskeletal disorders. The purpose of this study was to identify musculoskeletal complaints and to determine the risk level of work posture of workers at Borneo Laundry. The type of research used is descriptive qualitative, with the collection technique using NBM (Nordic Body Map) keisters which are used as an initial screening to provide an overview of complaints of musculoskeletal disorders, and the Rapid Entire Body Assessment (REBA) observation sheet and documentation to obtain posture risk level data. Work Research objects in this study were 3 Borneo Laundry workers. Based on the results of the Nordic Body Map (NBM) questionnaire, shows that 3 research objects experienced MSDs complaints, starting from “moderate” to “very high” MSDs complaints. Based on the Rapid Entire Body Assessment (REBA) method, it shows that 3 work processes have a "high" risk level for work posture and 3 work processes have a "medium" work posture risk level. So it can be concluded that it is necessary to take corrective action as soon as possible on the work posture of workers in Borneo Laundry, with the hope that the musculoskeletal complaints felt by workers will decrease, so that work productivity increases and health is maintained.